Improving Student Learning Outcomes in Science and Science Subjects Through a Problem-Based Learning Model for Class V.A SD Negeri 27 Palembang - Sari, Selvi Eka; Sari, Waliyyu Friska; Ashari, Turi; Sari, Yeni Permata; Hazari, Sheny Ayu; Erhami, Suci; Syarifuddin, Syarifuddin; Farma, Febriansyah (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2024)
This study aims to improve the learning outcomes of students in the subject of Natural and Social Sciences (IPAS) by applying the Problem-Based Learning (PBL) learning model in class V.A SD Negeri 27 Palembang. This research used the Classroom Action Research (CAR) method which was carried out in three cycles. Each cycle involved planning, implementation, observation, and reflection. For data analysis, both quantitative and qualitative approaches were employed.  The results showed a significant increase in students' learning outcomes in Chapter 2 “Harmony in Ecosystems”. The average score of students increased from 62.6 in cycle I with 62% learning completeness, to 70.1 in cycle II with 70% learning completeness, and reached 83.3 in cycle III with 83% learning completeness. Thus, the PBL learning model proved effective in improving student learning outcomes in IPAS subjects in class V.A SD Negeri 27 Palembang.